Malignant perivascular epithelioid cell tumour of the round ligament mimics leiomyoma on computed tomography - Nuttaya Pattamapaspong (2018)
We report a case of a 45-year-old woman who had a palpable mass in the left lower quadrant of the abdomen. Computed tomography (CT) showed a circumscribed mass in the left round ligament of the uterus. The mass had heterogeneous density and enhancement accompanied by mottled calcification, which was initially identified as a leiomyoma. A histopathological examination revealed a malignant perivascular epithelioid cell tumour (PEComa), which is a rare soft tissue tumour. This case demonstrates that the appearance of malignant PEComa on the CT can mimic leiomyoma, which is the most common tumour of the round ligament. To the best of our knowledge, this is the first report of a CT appearance of this round ligament tumour. The radiological features and differential diagnosis are discussed.